2020
DOI: 10.1371/journal.pone.0238769
|View full text |Cite
|
Sign up to set email alerts
|

Culture-dependent and -independent methods revealed an abundant myxobacterial community shaped by other bacteria and pH in Dinghushan acidic soils

Abstract: Myxobacteria are one of the most promising secondary metabolites producers. However, they are difficult to isolate and cultivate. To obtain more myxobacteria and know the effects of environmental factors on myxobacterial community, we characterized myxobacterial communities in Dinghushan acidic forest soils of pH 3.6–4.5 with culture-dependent and -independent techniques, and analyzed environmental factors shaping myxobacterial communities. A total of 21 myxobacteria were isolated using standard cultivation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…According to the latest taxonomic proposal, myxobacteria have been reclassified as the phylum Myxococcota , comprising the four orders Myxococcales , Polyangiales , Nannocystales , and Haliangiales , seven families, and 19 genera ( Waite et al, 2020 ). The three genera Myxococcus , Pyxidicoccus , and Corallococcus of the family Myxococcaceae have often been isolated from various habitats, and their 16S rRNA genes show highly homologous ( Mohr et al, 2016 , 2017 ; Livingstone et al, 2017 ; Wang et al, 2020 ). Compared with the 98.65% of 16S rRNA gene sequence similarity, the 98.7% of gyrB gene sequence similarity is suitable as the threshold for species boundaries of the three genera above ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest taxonomic proposal, myxobacteria have been reclassified as the phylum Myxococcota , comprising the four orders Myxococcales , Polyangiales , Nannocystales , and Haliangiales , seven families, and 19 genera ( Waite et al, 2020 ). The three genera Myxococcus , Pyxidicoccus , and Corallococcus of the family Myxococcaceae have often been isolated from various habitats, and their 16S rRNA genes show highly homologous ( Mohr et al, 2016 , 2017 ; Livingstone et al, 2017 ; Wang et al, 2020 ). Compared with the 98.65% of 16S rRNA gene sequence similarity, the 98.7% of gyrB gene sequence similarity is suitable as the threshold for species boundaries of the three genera above ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Abiotic factors such as pH and certain alkaline earth metals influence myxobacteria populations in soils and compost manure ( Zhang et al, 2013 ; Wang C. et al, 2020 ; Zhou et al, 2020 ; Dai et al, 2021 ). Increased actinorhodin production by Streptomyces coelicolor during co-culture conditions with M. xanthus has been associated with competitive acquisition of iron in soils ( Perez et al, 2011 ; Lee et al, 2020 ), and copper detoxification has been observed to improve M. xanthus predation of Sinorhizobium meliloti ( Contreras-Moreno et al, 2020 ).…”
Section: Environmental Factors That Influence Predationmentioning
confidence: 99%
“…Microbial community diversity is the most consistently observed environmental factor influencing myxobacteria abundance and diversity. Bacteria in ecological studies from numerous orders have been positively correlated to interact with myxobacteria including Anaerolineales , Burkholderiales , Cellvibrionales , Chitinophagales , Cytophagales , Flavobacteriales , Hyphomicrobiales, Ktedonobacterales , Pseudomonadales , Rhodospirillales , and Sphingomonadales ( Wang C. et al, 2020 ; Wang W. et al, 2020 ; Zhou et al, 2020 ; Dai et al, 2021 ). Often attributed to predatory preference of myxobacteria, connections between population-based ecological studies and predatory performance of myxobacteria remain unclear, and few environmental studies have provided genus-level correlations between myxobacteria and potential prey.…”
Section: Environmental Factors That Influence Predationmentioning
confidence: 99%
“…Furthermore, the type of fecal samples was reported as the main factor affecting the myxobacterial community structure in different fecal samples. Wang et al [ 9 ] studied the diversity of myxobacteria in Dinghushan by combining high-throughput sequencing and culture methods and found that the biological factors affecting the diversity of Dinghushan myxobacteria were mainly soil bacterial diversity, while the key abiotic factors were soil pH and the available potassium content. Ye et al [ 10 ] employed a Corallococcus sp.…”
Section: Introductionmentioning
confidence: 99%